PELAKSANAAN PROGRAM KREDIT USAHA PENINGKATAN KESEJAHTERAAN KELOMPOK USAHA EKONOMI PRODUKTIF IBU RUMAH TANGGA MISKIN PEDESAAN DI KABUPATEN BANTUL PROVINSI DAERAH ISTIMEWA YOGYAKARTA IMPLEMENTING WELFARE IMPROVEMENT BUSINESS CREDIT FOR PRODUCTIVE ECONOMIC BUSINESS GROUP OF RURAL POOR HOUSEWIFE PROGRAM IN BANTUL REGENCY YOGYAKARTA PROVINCE - Sedjati, Hari Walujo (Pembangunan Pedesaan, 2010)
Poverty in rural areas is a very fundamental problem. To overcome this problem, the Government of Bantul Regency conduct business credit program for improving the welfare of economically productive group of house-wife of poor households in rural areas. This program aims to poor communities accustomed uses banking services, capital raising efforts, and enhance ability to meet basic needs especially food. This study aims to analyzed the level of the programs success in achieving its objective. The research method is qualitative methods with interactive techniques. Results showed the program is experiencing a variety of barriers, because the loan amount is relatively small and short payback period. Also, the poor do not have good mental operations, such as willingness to work hard, expertise, adequate capital, frugality, perseverance, honesty, responsibility, and not risk large losses in trading.